2008
DOI: 10.1039/b809774g
|View full text |Cite
|
Sign up to set email alerts
|

Amorphization of faujasite at high pressure: an X-ray diffraction and Raman spectroscopy study

Abstract: International audienceIn situ X-ray diffraction and Raman spectroscopy measurements of synthetic powdered samples of faujasite 13X were carried out at high pressure using diamond anvil cells. Structural changes are detected, linked to a progressive reduction in crystallinity, before complete amorphization of the material. Three distinct compressibility regions are clearly observed, delimited by two discontinuities in the pressure dependence of the faujasite volume around 2 and 3.5 GPa. The transition from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 45 publications
3
48
0
Order By: Relevance
“…These results can explain the potential shock wave absorption properties of this material, as this local decompression partially 'absorbs' the applied static pressure. A similar apparent volume increase under pressure was previously reported also for zeolite A (Greaves et al, 2003;Greaves & Meneau, 2004) and faujasite (Isambert et al, 2008), even if the effect observed for silicalite-1-F -characterized by empty pores -is particularly marked. It must finally be underlined that the structural stability of loaded silicalite-1 -up to at least 25 GPa -is higher than that observed for the common, nonporous, tetrahedral forms of SiO 2 -cristobalite and -quartz, which undergoes a phase transition below this pressure at ambient temperature (Prokopenko et al, 2001;Kingma et al, 1993;Haines et al, 2001).…”
Section: Pressure-induced Amorphizationsupporting
confidence: 88%
“…These results can explain the potential shock wave absorption properties of this material, as this local decompression partially 'absorbs' the applied static pressure. A similar apparent volume increase under pressure was previously reported also for zeolite A (Greaves et al, 2003;Greaves & Meneau, 2004) and faujasite (Isambert et al, 2008), even if the effect observed for silicalite-1-F -characterized by empty pores -is particularly marked. It must finally be underlined that the structural stability of loaded silicalite-1 -up to at least 25 GPa -is higher than that observed for the common, nonporous, tetrahedral forms of SiO 2 -cristobalite and -quartz, which undergoes a phase transition below this pressure at ambient temperature (Prokopenko et al, 2001;Kingma et al, 1993;Haines et al, 2001).…”
Section: Pressure-induced Amorphizationsupporting
confidence: 88%
“…Due to the loss of X-ray diffraction signals resulting from the disappearance of long-range order upon PIA, 3,7,9,10 spectroscopic methods are extremely powerful to probe changes on a local level, especially by following the behaviour of molecules confined in the cages and channels of the porous structure. Below 2 GPa strong shifts in the three hydroxyl stretching components (n(OH)) between 3200 and 3600 cm À1 (Fig.…”
Section: X-ray Total Scatteringmentioning
confidence: 99%
“…The hydrated, charge-compensating Na + cations are located in various sites in the three-dimensional pore network, including the large supercage. Faujasite has been found to undergo pressure-induced amorphisation (PIA) at close to 2 GPa, by infrared 8 and Raman spectroscopy 10 and X-ray diffraction. 3,7,9,10 A further change from a low-density amorphous (LDA) to a high-density amorphous (HDA) form occurs in the pressure range between 2 and 4 GPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further high-P study on synthetic faujasite with composition Na 86 Si 106 Al 86 O 384 ·175H 2 O was undertaken by Isambert et al (2008), using in situ XRPD and Raman spectroscopy. The aim of the experiments was to study the P-induced amorphization process of faujasite.…”
Section: Hp-behaviour Of Zeolitesmentioning
confidence: 99%